Emergency upper urinary tract decompression: double-J stent or nephrostomy? A European YAU/ESUT/EULIS/BSIR survey among urologists and radiologists - ŞENER, TARIK EMRE (My University, 2022)
Purpose To evaluate the decompression of the pelvicalyceal system between urologists and radiologists. Methods A survey was distributed to urologists and to radiologists comparing double-J stent (DJS), percutaneous nephrostomy (PN) and primary ureteroscopy (URS) for three clinical scenarios (1-febrile hydronephrosis; 2-obstruction and persistent pain; 3-obstruction and anuria) before and after reading literature The survey included perception on radiation dose, cost and quality of life (QoL). Results Response rate was 40% (366/915). 93% of radiologists believe that DJS offers a better QOL compared to 70.6% of urologists (p = 0.006). 28.4% of urologists consider PN to be more expensive compared to 8.9% of radiologists (p = 0.006). 75% of radiologists believe that radiation exposure is higher with DJS as opposed to 33.9% of urologists. There was not a difference in the decompression preference in the first scenario. After reading the literature, 28.6% of radiologists changed their opinion compared to 5.2% of urologists (p < 0.001). The change favored DJS. In the second scenario, responders preferred equally DJS and they did not change their opinion. In the third scenario, 41% of radiologists chose PN as opposed to 12.6% of urologists (p < 0.001). After reading the literature, 17.9% of radiologists changed their opinion compared to 17.9% of urologists (p < 0.001), in favor of DJS. Although the majority of urologists (63.4%) consistently perform primary URS, only 3, 37 and 21% preferred it for the first, second and third scenarios, respectively. Conclusion The decision on the type of drainage of a stone-obstructing hydronephrosis should be individualized.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Urology; Pelvicalyceal obstruction; Decompression; Double-J stent; Percutaneous nephrostomy; Urologist; Radiologist; URETERAL STONE IMPACTION; PERCUTANEOUS NEPHROSTOMY; URETEROSCOPIC MANAGEMENT; HYDRONEPHROSIS; SEPSIS; OBSTRUCTION; DRAINAGE; OUTCOMES; CALCULI; NEPHROLITHOTOMY; Pelvicalyceal obstruction; Decompression; Double-J stent; Percutaneous nephrostomy; Urologist; Radiologist